RNA sequencing identifies gene regulatory networks controlling extracellular matrix synthesis in intervertebral disk tissues. Issue 5 (10th January 2018) - Riester, Scott M.; Lin, Yang; Wang, Wei; Cong, Lin; Mohamed Ali, Abdel‐Moneim; Peck, Sun H.; Smith, Lachlan J.; Currier, Bradford L.; Clark, Michelle; Huddleston, Paul; Krauss, William; Yaszemski, Michael J.; et al.
ABSTRACT: Degenerative disk disease of the spine is a major cause of back pain and disability. Optimization of regenerative medical therapies for degenerative disk disease requires a deep mechanistic understanding of the factors controlling the structural integrity of spinal tissues. In this investigation, we sought to identify candidate regulatory genes controlling extracellular matrix synthesis in spinal tissues. To achieve this goal we performed high throughput next generation RNA sequencing on 39 annulus fibrosus and 21 nucleus pulposus human tissue samples. Specimens were collected from patients undergoing surgical discectomy for the treatment of degenerative disk disease. Our studies identified associations between extracellular matrix genes, growth factors, and other important regulatory molecules. The fibrous matrix characteristic of annulus fibrosus was associated with expression of the growth factors platelet derived growth factor beta (PDGFB), vascular endothelial growth factor C (VEGFC), and fibroblast growth factor 9 (FGF9). Additionally we observed high expression of multiple signaling proteins involved in the NOTCH and WNT signaling cascades. Nucleus pulposus extracellular matrix related genes were associated with the expression of numerous diffusible growth factors largely associated with the transforming growth signaling cascade, including transforming factor alpha (TGFA), inhibin alpha (INHA), inhibin beta A (INHBA), bone morphogenetic proteins (BMP2, BMP6), and others. Clinical significance: this investigation provides important data on extracellular matrix gene regulatory networks in disk tissues. This information can be used to optimize pharmacologic, stem cell, and tissue engineering strategies for regeneration of the intervertebral disk and the treatment of back pain. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1356–1369, 2018.